2011
DOI: 10.1371/journal.pone.0021930
|View full text |Cite
|
Sign up to set email alerts
|

Small Compound 6-O-Angeloylplenolin Induces Mitotic Arrest and Exhibits Therapeutic Potentials in Multiple Myeloma

Abstract: BackgroundMultiple myeloma (MM) is a disease of cell cycle dysregulation while cell cycle modulation can be a target for MM therapy. In this study we investigated the effects and mechanisms of action of a sesquiterpene lactone 6-O-angeloylplenolin (6-OAP) on MM cells.Methodology/Principal FindingsMM cells were exposed to 6-OAP and cell cycle distribution were analyzed. The role for cyclin B1 to play in 6-OAP-caused mitotic arrest was tested by specific siRNA analyses in U266 cells. MM.1S cells co-incubated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 58 publications
1
49
0
Order By: Relevance
“…It also induced G1-phase cell-cycle arrest and apoptosis through inactive Akt and mitochondrial oxidative stress in cells of nasopharyngeal carcinoma [85]. The latter demonstrates the bio-effect of anti-cancer on inhibiting the proliferation of cancer cells in human colorectum, liver, stomach, lung and skin cancers [86], and on inducing cell apoptosis through a mitochondrial/caspase and NF-κB pathway in human HL-60 leukaemia and myeloma [87,88].…”
Section: Discussionmentioning
confidence: 87%
“…It also induced G1-phase cell-cycle arrest and apoptosis through inactive Akt and mitochondrial oxidative stress in cells of nasopharyngeal carcinoma [85]. The latter demonstrates the bio-effect of anti-cancer on inhibiting the proliferation of cancer cells in human colorectum, liver, stomach, lung and skin cancers [86], and on inducing cell apoptosis through a mitochondrial/caspase and NF-κB pathway in human HL-60 leukaemia and myeloma [87,88].…”
Section: Discussionmentioning
confidence: 87%
“…MTT assay was performed as described [31], and the IC 50 values were calculated using the CalcuSyn software (version 2.0, Biosoft, Cambridge, UK). Cell viability was estimated by trypan blue dye exclusion.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, 6-OAP was identified to inhibit the Jak2/Stat3 and Akt signaling pathways, thereby blocking the facilitation of the BM microenvironment on the MM cells. 6-OAP has also been found to induce marked inhibition of NF-κB in MM cells (5). However, to date, no studies have determined whether the inhibitory effects of 6-OAP on the cell cycle and certain signal pathways ultimately result in apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our preliminary study demonstrated that 6-OAP inhibits the proliferation of human MM cells by inducing the arrest of mitosis and inhibiting specific key pathways (5). However, whether 6-OAP-induced mitosis arrest and pathway inhibition are followed by apoptosis requires further study.…”
Section: Introductionmentioning
confidence: 94%